Entrepreneurial Leadership in Higher Education for Human Resource Improvement in Indonesia: A Narrative Literature Review - Tanti Sugiharti (Jurnal Visi Manajemen, 2024)
This narrative literature review examines the role of entrepreneurial leadership in Indonesian higher education as a strategic approach to enhancing human resource quality and national competitiveness. Amid rapid changes in the higher education landscape, entrepreneurial leadership emerges as a critical framework that integrates innovation, visionary thinking, calculated risk-taking, and collaborative governance. This leadership style fosters an institutional culture that encourages creativity, flexibility, and continuous improvement among faculty and students, aligning educational outcomes with labor market demands. The review synthesizes current research on how entrepreneurial leadership influences institutional strength, academic quality, and socio-economic development through partnerships involving universities, government, industry, and communities. It highlights challenges such as low entrepreneurial motivation among business students and the need for integrating practical entrepreneurial education effectively. Furthermore, digital transformation and internationalization are identified as key enablers for cultivating entrepreneurial mindsets and skills. The study underscores the importance of comprehensive policies, stakeholder engagement, and contextualized educational programs to support entrepreneurial ecosystems in higher education. Ultimately, fostering entrepreneurial leadership is essential for preparing graduates equipped with critical thinking, project management, and communication skills, thereby contributing to sustainable economic growth and innovation in Indonesia.